Structural and functional insights of STAT2-NS5 interaction for the identification of NS5 antagonist – An approach for restoring interferon signaling. (October 2020) - Choubey, Sanjay Kumar; Nachiappan, Mutharasappan; Richard, Mariadasse; Chitra, Jeyaraj Pandian; Jeyakanthan, Jeyaraman
Graphical abstract: Highlights: Protein-protein interaction of NS5-STAT2 complex playing major role in signaling mechanism for Dengue infection. The binding mode and potential interaction of NS5-STAT2 complex have been identified from the protein-protein docking studies. The MTase domain of NS5 protein have been targeted to prevent the host recognition of STAT2 protein in viral replication. The Identified compounds showed high binding score and energy compared to the reported inhibitor. The interactions of screened compounds is similar to the inhibitor bound crystal structure. Abstract: Dengue is a mosquito-borne viral infection caused by Dengue virus (DENV) and is an emerging concern in public health affecting billions of people worldwide annually with no effective drugs available till now. Immunogenic and highly conserved properties of Non-Structural Protein 5(NS5) in DENV makes it a potent marker to identify DENV infection. DENV interfere in the innate immune signaling and thereby decreases antiviral responses and favors viral replication. Viral recognition by host pathogen recognition receptors facilitates binding of interferon (IFN) to the interferon receptors that further activates both the Signal Transducer and Activator of Transcription-2 (STAT-2) a factor producing an antiviral response. The most debilitating factor of DENV infection is emaciation of human immune system by DENV- NS5. NS5 counters the antiviral response by STAT2 degradation impeding the transcriptional activation of interferon stimulated genes through interferon stimulated response elements. The present study aims to identify inhibitors for NS5 Methyl Transferase (MTase) domain and to provide an insight into the mechanism of STAT2 degradation in the host infected with DENV. Virtual screening and molecular docking studies identified five potential inhibitors ZINC84154300, ZINC08762321, ZINC08762323, ZINC12659408 and ZINC12285470 with docking scores of -10.55, -10.53, -10.78, -11.28 and -10.78 kcal/mol respectively. To further investigate the stability of the complexes, we have used Molecular Dynamics Simulations (MD). Besides, the binding free energy of top 5 docked ligands were estimated through Molecular Mechanics Generalized Born and Surface Area Solvation (MM/GBSA) methods. This study also provides an insight on the mechanism of immunological processes involved in alleviating the antiviral immune response and computational identification of potent inhibitors for viral NS5 protein.